Correlation Between Increased Homing Flight Duration and Altered Gene Expression in the Brain of Honey Bee Foragers After Acute Oral Exposure to Thiacloprid and Thiamethoxam - Christen, Verena; Grossar, Daniela; Charrière, Jean-Daniel; Eyer, Michael; Jeker, Lukas (Frontiers in Insect Science, 2021)
Neonicotinoids as thiamethoxam and thiacloprid are suspected to be implicated in the decline of honey bee populations. As nicotinic acetylcholine receptor agonists, they disturb acetylcholine receptor signaling in insects, leading to neurotoxicity and are therefore globally used as insecticides. Several behavioral studies have shown links between neonicotinoid exposure of bees and adverse effects on foraging activity, homing flight performance and reproduction, but the molecular aspects underlying these effects are not well-understood. In the last years, several studies through us and others showed the effects of exposure to neonicotinoids on gene expression in the brain of honey bees. Transcripts of acetylcholine receptors, hormonal regulation, stress markers, detoxification enzymes, immune system related genes and transcripts of the energy metabolism were altered after neonicotinoid exposure. To elucidate the link between homing flight performance and shifts in gene expression in the brain of honey bees after neonicotinoid exposure, we combined homing flight activity experiments applying RFID technology and gene expression analysis. We analyzed the expression of endocrine factors, stress genes, detoxification enzymes and genes linked to energy metabolism in forager bees after homing flight experiments. Three different experiments (experiment I: pilot study; experiment II: “worst-case” study and experiment III: laboratory study) were performed. In a pilot study, we wanted to investigate if we could see differences in gene expression between controls and exposed bees (experiment I). This first study was followed by a so-called “worst-case” study (experiment II), where we investigated mainly differences in the expression of transcripts linked to energy metabolism between fast and slow returning foragers. We found a correlation between homing flight duration and the expression of cytochrome c oxidase subunit 5A, one transcript linked to oxidative phosphorylation. In the third experiment (experiment III), foragers were exposed in the laboratory to 1 ng/bee thiamethoxam and 8 ng/bee thiacloprid followed by gene expression analysis without a subsequent flight experiment. We could partially confirm the induction of cytochrome c oxidase subunit 5A, which we detected in experiment II. In addition, we analyzed the effect of the feeding mode (group feeding vs. single bee feeding) on data scattering and demonstrated that single bee feeding is superior to group feeding as it significantly reduces variability in gene expression. Based on the data, we thus hypothesize that the disruption of energy metabolism may be one reason for a prolongation of homing flight duration in neonicotinoid treated bees.